Study on antifriction mechanism of lubricating wear-resistant coating with parallel texture. Issue 5 (10th August 2015) - Zhao, Yuncai; Yang, Fei; Guo, Yongming
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the effects of parallel texturing coating on antifriction mechanism of lubricating wear-resistant coating. Design/methodology/approach – A KF301/WS2 lubricating wear-resisting coating was prepared on matrix material GCr15 by applying supersonic plasma spraying technology. On the basis of this sample, the KF301/WS2 modified coating with parallel pit-type texture was prepared by laser re-melting technology and a surface texturing technique. Their friction and wear behaviors were evaluated under ambient temperature, and the antifriction mechanism of two kinds of coatings were discussed. Findings – Results showed that parallel texture has a certain impact on the tribological properties of the coating. When friction and wear reach stable state, the value of the friction coefficient of conventional coating was 0.115, while that of parallel texturing coating was 0.09, the latter decreased by 21 per cent. When the friction and wear time was up to 4 hours, the wear loss of the conventional coating was 0.29 mg, while that of the parallel texturing coating was 0.13 mg, the latter decreased by 55 per cent. Originality/value – The tribological properties of parallel texturing coating were higher than conventional coating. That is because the change of three-body layer reduces the friction coefficient and the abrasive particles were collected by parallel texture, reducing the effects of debris.